Comparison of Saline Infusion Sonohisterography (SIS) and Histeroscopy Examination in Abnormal Uterine Bleeding - Trisanto, Apdhika Kristian; Tjahjanto, Hary (Faculty of Medicine, Diponegoro University, 2022)
Introduction: Abnormal uterine bleeding (AUB) is bleeding from the uterus that is longer than usual or that occurs at an irregular time, affecting 20% of the adolescent age group, and 50% of women aged 40-50 years in Indonesia. The causes of AUB are pregnancy, anovulatory dysfunction, uterine leiomyoma, endometrial polyps, endometrial hyperplasia, or endometrial carcinoma. This study aims to compare the accuracy of Saline Infusion Sonohysterography (SIS), hysteroscopy and endometrial histopathology in determining pathological abnormalities in women with AUB.Material and Method: This cross sectional diagnostic study was conducted at General Hospital dr. Kariadi Semarang and its network hospitals in June 2020. Samples were determined by consecutive sampling, including married women, not pregnant, had no genital infection and did not present with any malignancy. Histopathological examination of the endometrium is the gold standard for AUB diagnosis. Research data were obtained from secondary data from patient's medical records including demographic characteristics, clinical history, pregnancy history, SIS examination data, hysteroscopy and endometrial histopathology.Result: There were 51 subjects with a mean age of 31.67 ± 5.21 years. The most common complaints were intermenstrual bleeding (37.3%), followed by irregular menstrual bleeding (21.6%), heavy menstrual bleeding (13.7%), and amenorrhea (5.9%). Sensitivity value of SIS examination ranged from 81.5-100% and specificity ranged from 30.77-100%. Hysteroscopy has a sensitivity value range of 87.5-98% and a specificity value of 62.5-100%.Conclusion: SIS examination could be an alternative for endometrial structural abnormalities diagnosis in AUB if hysteroscopy is unavailable.